Water Scarcity: A Global Threat - Muhammad Rameez Mohsin; Salman Khan; Rizwan ul Haq Aamir; Maaz Mohsin; Syed Kamran Haider (Social Science Review Archives, 2025)
Water is an unavoidable need of life and water scarcity means a lack of fresh and drinkable water. Water scarcity is turning out to be a global threat as almost all the important and populous regions of the world like Asia, Africa, the Middle East, etc. are facing the issues of water scarcity and water-based conflicts. There have been more than 35 violent inter-state water disputes in the last 50 years. The major causes of water scarcity are an increase in demand, water overuse, climate change, and a decrease in supply. The problem of scarcity of water is increasing day by day which depicts that if this possible water crisis is not solved peacefully and appropriately it will lead to global conflicts because every water-scarce country would try to capture the water resources of other countries for meeting its own needs and survival. This paper highlights the importance of water and focuses on how the careless attitude and mismanagement of water resources can result in a global disaster.